The cost effectiveness of NHS physiotherapy support for occupational health (OH) services - Phillips Ceri J; Phillips (nee Buck) Rhiannon; Main Chris J; Watson Paul J; Davies Shân; Farr Angela; Harper Christie; Noble Gareth; Aylward Mansel; Packman Julie; Downton Matt; Hale Janine (BMC Musculoskeletal Disorders, 2012)
Abstract Background Musculoskeletal pain is detrimental to quality of life (QOL) and disruptive to activities of daily living. It also places a major economic burden on healthcare systems and wider society. In 2006, the Welsh Assembly Government (WAG) established a three tiered self-referral Occupational Health Physiotherapy Pilot Project (OHPPP) comprising: 1.) telephone advice and triage, 2.) face-to-face physiotherapy assessment and treatment if required, and 3.) workplace assessment and a return-to-work facilitation package as appropriate. This study aimed to evaluate the feasibility and cost-effectiveness of the pilot service. Methods A pragmatic cohort study was undertaken, with all OHPPP service users between September 2008 and February 2009 being invited to participate. Participants were assessed on clinical status, yellow flags, sickness absence and work performance at baseline, after treatment and at 3 month follow up. Cost-effectiveness was evaluated from both top-down and bottom-up perspectives and cost per Quality Adjusted Life Year (cost/QALY) was calculated. The cost-effectiveness analysis assessed the increase in service cost that would be necessary before the cost-effectiveness of the service was compromised. Results A total of 515 patients completed questionnaires at baseline. Of these, 486 were referred for face to face assessment with a physiotherapist and were included in the analysis for the current study. 264 (54.3%) and 199 (40.9%) were retained at end of treatment and 3 month follow up respectively. An improvement was observed at follow up in all the clinical outcomes assessed, as well as a reduction in healthcare resource usage and sickness absence, and improvement in self-reported work performance. Multivariate regression indicated that baseline and current physical health were associated with work-related outcomes at follow up. The costs of the service were £194-£360 per service user depending on the method used, and the health gains contributed to a cost/QALY of £1386-£7760, which would represent value for money according to current UK thresholds. Sensitivity analyses demonstrated that the service would remain cost effective until the service costs were increased to 160% per user. Conclusions This pragmatic evaluation of the OHPPP indicated that it was likely to be feasible in terms of service usage and could potentially be cost effective in terms of QALYs. Further, the study confirmed that improving physical health status for musculoskeletal pain patients is important in reducing problems with work capacity and related costs. This study suggests that this type of service could be potentially be useful in reducing the burden of pain and should be further investigated, ideally via randomised controlled trials assessing effectiveness and cost-effectiveness.